Owning Up to Negative Ingroup Traits: How Personal Autonomy Promotes the Integration of Group Identity. Issue 5 (15th September 2016) - Legault, Lisa; Weinstein, Netta; Mitchell, Jahlil; Inzlicht, Michael; Pyke, Kristen; Upal, Afzal
Abstract: Objective: Our experiences, attributes, and behaviors are diverse, inconsistent, and often negative. Consequently, our capacity to assimilate divergent experiences—particularly negative aspects—is important to the development of a unified self. Whereas this process of integration has received attention at the level of personal identity, it has not been assessed at the level of group identity. Objective: We examined the mechanisms involved in integrating positive and negative ingroup identities, as well as related outcomes. Method: In three experiments, participants ( N  = 332) high and low in autonomy identified either positive or negative aspects of their ingroup and then indicated the extent to which they integrated the attribute. Results: Those high in personal autonomy integrated both positive and negative identities, whereas those low in autonomy acknowledged only positive identities. Study 2 showed that, regardless of identity valence, those high in autonomy felt satisfied and close with their group. Conversely, those low in autonomy felt less close and more dissatisfied with their group after reflecting on negative identities. Finally, reflecting on a negative identity reduced prejudice, but only for those high in autonomy. Conclusions: Owning up to negative group traits is facilitated by autonomy and demonstrates benefits for ingroup and intergroup processes.